2016
DOI: 10.1108/ijbm-04-2015-0063
|View full text |Cite
|
Sign up to set email alerts
|

Mobile claim management adoption in emerging insurance markets

Abstract: Purpose – The purpose of this paper is to explore the adoption of a mobile insurance claim system (M-insurance) and develops a framework for the adoption of M-insurance by consumers. Design/methodology/approach – This study assesses mobile technology for claim management through the lens of the technology acceptance model (TAM) and diffusion of innovation (DOI) models as a major guideline, using exploratory research through in-depth inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Semi-structured interviews (Bennett and Sung, 2013) were carried out with a sample of customers of FTSs (N = 14) to collect detailed information to better understand their behavioral, normative and control beliefs about FTSs (Gowanit et al, 2016;Drew, 2014). These interviews aimed to understand the beliefs behind the intention to purchase FTSs, develop the foundations for the quantitative phase of this study and refine the research problem (Farah, 2017;Weischedel et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured interviews (Bennett and Sung, 2013) were carried out with a sample of customers of FTSs (N = 14) to collect detailed information to better understand their behavioral, normative and control beliefs about FTSs (Gowanit et al, 2016;Drew, 2014). These interviews aimed to understand the beliefs behind the intention to purchase FTSs, develop the foundations for the quantitative phase of this study and refine the research problem (Farah, 2017;Weischedel et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…It is evident that insurance businesses can utilise mobile technologies to enhance the effectiveness and efficiency at work. Previous research in insurance industry found several determinants that affect such technologies adoption (Liang, Huang, Yeh & Lin, 2007;Gowanit et al, 2016;Yueh, Lu & Lin, 2016); Visvanathan & Van Der Merwe, 2018). However, there are still limited studies conducted to discover determinants that initiate the usage, improve the present usage and advance a constant usage among employees and agents in the insurance industry.…”
Section: Problem Statementmentioning
confidence: 99%
“…Mobile technologies play vital roles in enhancing business processes across various industries, including the competitive insurance industry in which mobile technologies are utilized to improve efficiency of office employees along with its processes (Visvanathan & Van Der Merwe, 2018). Gowanit, Thawesaengskulthai, Sophatsathit and Chaiyawat (2016) promoted that insurance businesses are able to ride on mobile technologies seamlessly as most of the transactions and processes can be completed electronically; hence mobile technologies has been the most important change in the industry. This is supported by Thiangtam et al (2017) and Lu et al (2018) who expect fully electronic-based business models for the insurance industry in the near future, thereby strengthening the role of mobile technologies in insurances businesses.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Davis et al (1989) tailored TAM into information system context and designed to predict information technology acceptance and usage on the job. TAM has been widely applied to a diverse set of technologies and users (Gebauer and Shaw, 2004;Cheng, 2015;Kansal, 2016;Lai, 2017;Maditinos et al, 2013;Wu and Wang, 2005;Wu, 2011;Caniëls et al, 2015;Ifinedo, 2011;Dahnil et al, 2014;Celuch et al, 2013;Hayes, 2012;Khader, 2015;Hung et al, 2014;Kaushik and Rahman, 2015;Abbasi et al, 2015;Ma et al, 2017;Gupta et al, 2016;Marakarkandy et al, 2017;Gowanit et al, 2016;Ozturk, 2016;Kim and Shin, 2015).…”
Section: Introductionmentioning
confidence: 99%